(untitled) (International Journal of Atharva, 2024)
Introduction: This study investigates the nutrition knowledge and dietary practices among secondary-level school students, a demographic prone to unhealthy habits such as junk food consumption, meal skipping for weight loss, and non-compliance with balanced diets. These behaviors increase the risk of non-communicable diseases like obesity and diabetes in adolescents. This study has aims to examine the nutrition knowledge and dietary practices of secondary-level school students, a demographic that is increasingly susceptible to unhealthy eating habits. Specifically, it focuses on behaviors such as junk food consumption, meal skipping for weight loss, and the neglect of balanced diets. These specific practices contribute to a heightened risk of non-communicable diseases, including obesity and diabetes, among adolescents. Methodology: The quantitative research approach was employed an exploratory design, analyzing data from 121 students in Kathmandu valley using a close-ended questionnaire during 7th April to 28th May 2024. The systematic sampling technique was used, and respondents were selected by using a lottery system. As a result, Grade 11 was picked up randomly. Descriptive analyses were made to describe the practices of the students. Result (s): Study indicates that out of 121 respondents, about near to half (48.8%) were male and little more than half (51.2%) were female. Similarly, there were no significant relationship exists between nutrition knowledge and dietary practices among the students. Likewise, independent variables such as age, gender, and religion do not significantly influence either nutrition knowledge or dietary practices. Despite the students’ understanding of nutrition, this knowledge does not translate into healthier eating behaviors. Conclusion and recommendation: The study reveals that there are notable gaps in their knowledge, particularly regarding the energy content of fat-free foods, the role of dietary fiber, and the impact of empty-calorie foods and meal-skipping on health. Likewise, findings highlight the disconnect between what students know about nutrition and how they apply it in their daily lives, suggesting the need for more effective interventions to encourage healthier dietary practices. Moreover, targeted nutritional education programs at school could address these gaps in knowledge and encourage healthier dietary practices.